A LoRaWAN-Based Infrastructure for Meteorological Data Collection to Support Software Systems in Agriculture - Kuhn, Mateus D.; Chequin, Marcelo P.; Hart, Marcos V.; Battisti, Gerson; Roos-Frantz, Fabricia; Frantz, Rafael Z.; Sawicki, Sandro (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2026: Anais do XXIX Congresso Ibero-Americano em Engenharia de Software, 2026)
This paper describes the deployment of a LoRaWAN-based infrastructure in the municipality of Santa Rosa, RS, Brazil, integrating meteorological stations, gateways distributed across urban and rural areas, and a software stack composed of ChirpStack, Node-RED, and PostgreSQL for continuous environmental data acquisition. Unlike purely conceptual approaches, this work presents a real operational environment and its applications. The collected data include temperature, humidity, precipitation, wind, luminosity, and UV radiation, which are made available through dashboards for real-time monitoring. The main contributions are: (i) the implementation of a functional infrastructure, (ii) support for agricultural applications based on real-world data, and (iii) the identification of indicators and use cases to support decision-making, such as phytosanitary risk analysis. Finally, perspectives for system evolution, evaluation, and future research are discussed.